2021
DOI: 10.3390/ijms22115766
|View full text |Cite
|
Sign up to set email alerts
|

Ubiquitin-Specific Protease 29 Regulates Cdc25A-Mediated Tumorigenesis

Abstract: Cell division cycle 25A (Cdc25A) is a dual-specificity phosphatase that is overexpressed in several cancer cells and promotes tumorigenesis. In normal cells, Cdc25A expression is regulated tightly, but the changes in expression patterns in cancer cells that lead to tumorigenesis are unknown. In this study, we showed that ubiquitin-specific protease 29 (USP29) stabilized Cdc25A protein expression in cancer cell lines by protecting it from ubiquitin-mediated proteasomal degradation. The presence of USP29 effecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…[ 17 ] In a cervical cancer study, the overexpression of USP29 enables the stabilization of the cell division cycle 25A (Cdc25A) and enhances the oncogenic potential of HeLa cells. [ 18 ] In addition, USP29 was reported to promote gastric cancer cell migration by cooperating with phosphatase SCP1 to stabilize Snail protein. [ 20 ] However, we found that the knockdown of USP29 significantly decreased the protein level of TWIST1, but only slightly affected the protein level of Snail1 in MDA‐MB‐231 and BT549 cells (Figure S2D, Supporting Information).…”
Section: Discussionmentioning
confidence: 99%
“…[ 17 ] In a cervical cancer study, the overexpression of USP29 enables the stabilization of the cell division cycle 25A (Cdc25A) and enhances the oncogenic potential of HeLa cells. [ 18 ] In addition, USP29 was reported to promote gastric cancer cell migration by cooperating with phosphatase SCP1 to stabilize Snail protein. [ 20 ] However, we found that the knockdown of USP29 significantly decreased the protein level of TWIST1, but only slightly affected the protein level of Snail1 in MDA‐MB‐231 and BT549 cells (Figure S2D, Supporting Information).…”
Section: Discussionmentioning
confidence: 99%
“…Song et al [ 95 ] showed that NPAS2 was up-regulated in AML patients compared to controls, and that NPAS2 knockdown in AML cells led to cell cycle arrest at the G1 and G2 phases, as well as apoptosis in leukemic cells, which may suggest the participation of this gene in the development of leukemia, demonstrating its possible role as biomarker of the disease. Moreover, the study also investigated the role of NPAS2 in the cell division cycle 25A (CDC25A), a dual-specificity phosphatase that participates in the progression of the G1 to the S phase together with CDKs, and which may have its expression regulated by transcription factors [ 139 , 140 , 141 , 142 ]. High levels of CDC25A have already been reported in tumorigenic cells [ 143 , 144 , 145 , 146 , 147 ].…”
Section: Discussionmentioning
confidence: 99%
“…Mechanistically, USP29 promoted Cdc25A-dependent cell cycle progression by regulating the protein stability of Cdc25A. 29 USP29 was highly upregulated in colon cancer tissues and promoted cancer cell proliferation; although the detailed mechanism was unclear, USP29 depletion was reported to delay cell cycle progression. 17 Recently, another study for colon cancer presented the accordant result that USP29 facilitates the malignant proliferation of cancer cells by upregulating the KIAA1429/SOX8 axis both in vitro and in vivo.…”
Section: Cell Cycle and Proliferationmentioning
confidence: 99%
“…In cervical cancer HeLa cells, depletion of USP29 induced an impaired G1‐S phage transition and an accumulation of cells at G0/G1 phase, and this was rescued by reconstituted cell division cycle 25A (Cdc25A), which is a regulator of cell cycle progression. Mechanistically, USP29 promoted Cdc25A‐dependent cell cycle progression by regulating the protein stability of Cdc25A 29 . USP29 was highly upregulated in colon cancer tissues and promoted cancer cell proliferation; although the detailed mechanism was unclear, USP29 depletion was reported to delay cell cycle progression 17 .…”
Section: Usp29 In Cancermentioning
confidence: 99%